Biomass-derived porous carbon materials with sulfur and nitrogen dual-doping for energy storage. Issue 3 (8th January 2015) - Xu, Guiyin; Han, Jinpeng; Ding, Bing; Nie, Ping; Pan, Jin; Dou, Hui; Li, Hongsen; Zhang, Xiaogang
Abstract : Biomass-derived porous carbon material with sulfur and nitrogen dual-doping exhibits great potential for energy storage devices. Abstract : Nowadays, energy shortage is a serious socioeconomic problem. The recovery of biomass can make a very significant contribution in alleviating the burden on already-strained energy resources. Broad beans, which are abundant in amino acids and vitamins, are extensively cultivated worldwide. However, a large quantity of by-product, broad bean shells, remains unused and pollutes the environment from the incinerating and/or uncontrolled decomposition that results. In this paper, we report the synthesis of sulfur and nitrogen dual-doping porous carbon materials, for use as the electrode materials of energy storage devices, produced by carbonizing the shells of broad beans by a chemical activation. The specific capacitance of the as-prepared porous carbon material is as high as 202 F g −1, with a superior cycling performance for electric double layer capacitors at a current density of 0.5 A g −1 . Furthermore, it also shows a stable performance for lithium ion batteries and sodium ion batteries, which suggests that it has a promising potential for wide applications in the field of energy storage devices.